What is the right to food? - Kent, George (World Nutrition, 2022)
On October 28, 2022 Michael Fakhri, the United Nations Special Rapporteur on the Right to Food presented a report to the United Nations General Assembly, the highest level of governance in the world (Fakhri, Michael 2022).  He called on the United Nations system to strengthen its efforts to ensure fulfillment of the right to food. These Special Rapporteurs have led the efforts for many years. In 2005 I published a book titled Freedom From Want: The Human Right to Adequate food. (Kent 2005). Its preface was written by Jean Zeigler, the first United Nations Special Rapporteur on the Right to Food, starting in 2000. He summarized my book, with a conclusion that in effect introduces this commentary: “Human rights are not only unashamedly utopian, but also eminently practical. Human rights can make a difference. It is time to make the right to food a reality.” This commentary discusses how the goal of making the right to food a reality could be expedited by developing a clear and widely shared understanding of what it means.